Explosive Vomiting Associated with Proximal Colonic Distention during a Difficult Propofol-Assisted Colonoscopy - Kang H. Rah; William Ferges; James Tse (Case Reports in Anesthesiology)
We present a case of explosive vomiting associated with the extensive manipulation of the proximal colon during a difficult colonoscopy procedure. The cause of vomiting in this case may have been multifactorial; however, proximal colonic distention was the most likely factor because the onset of vomiting coincided with proximal colonic manipulation and happened without any prodromal signs, coughing, and airway obstruction. Propofol, the sedative most commonly administered to the patient during colonoscopy, allows for a deep state of sedation, and consequently extensive colonic distention and scope manipulation. Colonic distention may lead to a higher risk of vomiting. We reviewed the neurocircuitry associated with vomiting and discussed why proximal colonic distention may increase the risk of vomiting. We emphasize vigilance during the manipulation of the proximal colon because vomiting increases the potential for aspiration pneumonitis and pneumonia in patients under deep propofol sedation with attenuated airway responses.